(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The research focuses on the attitudes and readiness of organizations to integrate Artificial Intelligence (AI) technology into their internal business processes. The present study aims to determine how organizations perceive technological innovations related to AI. Specific goals include measuring the degree of readiness and acceptance of technological innovations by organizations, as well as identifying factors influencing the success or failure of this process. The main object is AI technology and its potential for enhancing the efficiency of internal business process management. The significance of this analysis is threefold, providing valuable information on current trends and challenges in internal business processes and their transformation under the influence of AI. In the course of the study shall be justified the thesis that AI technology holds significant potential for optimizing internal business processes, that is not yet fully realized and utilized due to various obstacles. Overcoming these obstacles is possible through individualized strategies, the establishment of ethical standards, active training, and other measures that contribute to the successful integration of artificial intelligence into organizational dynamics. The methodology includes a comprehensive literature review combined with the use of questionnaire surveys, Gap analysis and SWOT analysis. The main conclusions are related to the diversity in motivations among surveyed companies, necessitating differentiated strategies. Improving operational efficiency and customer service, and enhancing competitiveness, transpire as driving power for AI implementation. Evaluating attitudes reveals differences in readiness among business organizations, resp. some of them actively taking steps to implement AI, while others are still exploring possibilities or are uncertain about the overall approach to adopt. The recommendations for organizations are multifaceted. Constantly exploring new technologies and updating approaches are necessary for a sustainable transition to more intelligent business process management.